Expanding Stroke Preparedness to Vulnerable Populations: A Music Video for the Deaf Community - Mellanie V. Springer; Casey L. Corches; Bernadette McCracklin; Melecia Scott; Maria Cielito Robles; Lesli E. Skolarus (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Acute stroke treatments reduce disability after stroke, but eligibility for these treatments depends on rapid hospital arrival after symptom onset. Stroke preparedness interventions teach stroke symptoms and the importance of calling 911, thereby increasing patient eligibility for stroke treatments. Stroke preparedness interventions for the Deaf community are lacking. We sought to adapt a stroke preparedness music video, which was initially created for the hearing, for the Deaf community. Methods and Results We used a community‐engaged approach, partnering with members of the Deaf community, to adapt the video over 4 months. Adaptation involved assessing the comprehensibility and appropriateness of the video and interpreting the song lyrics into American Sign Language. Conclusions We collaborated with the Deaf community to create a stroke preparedness video for the Deaf. Future research will involve refining the video and testing its efficacy to increase stroke symptom recognition and intent to call 911.